Climate of Accountability, Respect, and Ethics Survey (CARES): development and validation of an organizational climate survey - Martinson, Brian C.; Smallfield, Jarvis; Magley, Vicki J.; Thrush, Carol R.; Gunsalus, C. K. (Frontiers in Research Metrics and Analytics, 2025)
BackgroundThis research describes the development and validation of the CARES Climate Survey, a 22-item measure designed to assess interpersonal dimensions of work-unit climates. Dimensions of work-unit climates are identified through work-unit member perceptions and include civility, interpersonal accountability, conflict resolution, and institutional harassment responsiveness.MethodsTwo samples (N = 1,384; N = 868) of academic researchers, including one from the North American membership of the American Geophysical Union (AGU), and one from a large research-intensive university, responded to the CARES and additional measures via an online survey.ResultsWe demonstrate content validity of the CARES measure and confirm structural validity through exploratory and confirmatory factor analyses which yielded four dimensions of interpersonal climate. In addition, we confirm the CARES internal reliability, construct validity, and excellent sub-group invariance.ConclusionsThe CARES is a brief, psychometrically sound instrument that can be used by researchers, institutional leaders, and other practitioners to assess interpersonal climates in organizational work-units.Originality/valueThis is the first study to develop and validate such a measure of interpersonal climates specifically in research-intensive organizations, using rigorous psychometric methods, grounded in both theory and prior research on work-unit climates.